Desenho universal para a aprendizagem no ensino de ciências: estratégias para o estudo do sistema digestório - (:unkn) unknown (Universidade Federal do Pampa, 2018)
This work presents a didactic sequence for Science Education created using Universal Design for Learning (UDL) - a practical and theoretical framework that proposes the organizing of pedagogical practices that are accessible and promote learning for all students. This framework is organized in three main principles, as follows: provide multiple ways of Representation (the "what" of learning), provide multiple means of action and expression (the "how" of learning) and provide multiple means of self development (the "why" of learning). The study was conducted through a pedagogical intervention research that sought to plan, implement and evaluate the proposal using the principles of UDL, approaching the subject of the digestive system to an eighth grade class in Middle School, identifying contributions and limitations of the framework in the construction of the subject's scientific concepts. The Didactic Sequence was planned for students with varied cognitive styles and deficiencies, including deafness and intelectual deficiency. Each principle was approached with varied activities. The evaluation took place throughout whole process as verification lists and qualitative assessment tools were used. The data of the investigation were collected using instruments such as observation, multiple choice questions, field diary and documental analysis, and analyzed through subject analysis. The study proved that the principles of UDL can aid Science Education and its strategies were very important for the students' construction of learning.
Keywords: Desenho universal para a aprendizagem; Ensino de ciências; Estratégias de aprendizagem; Universal design for learning; Science education; Learning strategies; CNPQ::CIENCIAS DA SAUDE